Ore resource modelling of Ajabanoko iron ore deposit, Ajabanoko, Nigeria - Rasheed Adeshina, Adebimpe; Jide Muili, Akande (International Journal of Engineering and Technology, 2020)
Ore resource modelling is an essential aspect of mining operation. It is also a crucial pre-mining step required for a successful exploitation of mineral deposits. Ajabanoko iron ore resource model was developed and the ore reserve estimate carried out using inverse distance method as contained in Surpac 6.4.1 mine software. The total number of blocks used for the model is 54,475. Ore estimation result obtained from thirteen drill hole data indicates 38,313,595 tonnes of iron ore and density of 3.65 tonnes/m3. The average grade and total volume of the ore body is 36.36 % and 10,496,595 m3 respectively.Â Â